Social status and institutional foundations of the constitution’s 1980: A compromise proposal - Pfeffer Urquiaga, Emilio; Lizama Allende, Felipe (Derecho Público Iberoamericano, 2015)
This article argues that the welfare State is perfectly compatible with the foundations of the 1980 Constitution. Moreover, an examination of its principles demands it.